The ‘step-clipping’ method: a guide for identifying a previously bleeding colonic diverticulum - Tamari, Hirosato; Aoyama, Taiki; Shigita, Kenjiro; Asayama, Naoki; Fukumoto, Akira; Mukai, Shinichi; Nagata, Shinji (Endoscopy International Open, 2020)
Background and study aims Unsatisfactory detectability of a previously bleeding diverticulum by colonoscopy results from difficulty in precisely locating the target lesion, even with presence of an extravasation on contrast-enhanced computed tomography (CECT). This study aimed to evaluate the usefulness of the step-clipping method to overcome this limitation.Patients and methods Step-clipping was indicated for patients with colonic diverticular bleeding and presence of extravasation on CECT, but with absence of active bleeding on subsequent colonoscopy. The target diverticulum was identified by comparing computed tomography images before and after step clipping, which provided a positional relationship between each clip and the target lesion.Results Based on data from 21 consecutive cases meeting our inclusion criteria (14 men and 7 women; mean age, 73.2 years), the target diverticulum was endoscopically identified in 20 cases (95 %), in a median time of 5 minutes, and successfully treated. No adverse events were observed with the step-clipping method.Conclusion Step-clipping provided easy guidance to the target site for treatment in a short time, despite spontaneous cessation of bleeding at the diverticulum.